Optimal Sizing of a Photovoltaic-Hydrogen Power System for HALE Aircraft by means of Particle Swarm Optimization. (19th April 2015) - Sanchez, Victor M.; Barbosa, Romeli; Cruz, J. C.; Chan, F.; Hernandez, J.
Abstract : Over the last decade there has been a growing interest in the research of feasibility to use high altitude long endurance (HALE) aircrafts in order to provide mobile communications. The use of HALEs for telecommunication networks has the potential to deliver a wide range of communication services (from high-quality voice to high-definition videos, as well as high-data-rate wireless channels) cost effectively. One of the main challenges of this technology is to design its power supply system, which must provide the enough energy for long time flights in a reliable way. In this paper a photovoltaic/hydrogen system is proposed as power system for a HALE aircraft due its high power density characteristic. In order to obtain the optimal sizing for photovoltaic/hydrogen system a particle swarm optimizer (PSO) is used. As a case study, theoretical design of the photovoltaic/hydrogen power system for three different HALE aircrafts located at 18° latitude is presented. At this latitude, the range of solar radiation intensity was from 310 to 450 Wh/sq· m/day. The results obtained show that the photovoltaic/hydrogen systems calculated by PSO can operate during one year with efficacies ranging between 45.82% and 47.81%. The obtained sizing result ensures that the photovoltaic/hydrogen system supplies adequate energy for HALE aircrafts.